2019
DOI: 10.1111/bcpt.13286
|View full text |Cite
|
Sign up to set email alerts
|

ZFAS1 knockdown inhibits viability and enhances cisplatin cytotoxicity by up‐regulating miR‐432‐5p in glioma cells

Abstract: Background Long non‐coding RNA (lncRNA) zinc finger antisense 1 (ZFAS1) is a novel vital oncogenic lncRNA that is dysregulated in various types of cancers, including glioma. According to TargetScan prediction, miR‐432‐5p is a target of ZFAS1. Herein, we aimed to determine whether there was a correlation between ZFAS1 and miR‐432‐5p and to explore their roles in glioma. Methods The expression levels of ZFAS1 and microRNA (miR)‐432‐5p in clinical tissues and cell lines were measured using RT‐qPCR. Cell viability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…It has also been reported that miR-432-5p was implicated in facilitating cell progression by activating Wnt/β-catenin signaling and promoting cell growth and metastasis in human hepatocellular carcinoma (33,34). Yang et al reported that lower levels of miR-432-5p were observed in both glioma tissues and cells (35), and it has been extensively reported that translocation t(X;17)(p11;q25) of ASPSCR1 with transcription factor TFE3 gene results in a ASPSCR1-TFE3 fusion protein in alveolar soft part sarcoma and in renal cell carcinomas (36,37). ZNF384related fusion genes were detected in acute lymphoblastic leukemia (38), and GALNT9 was demonstrated to be well conserved in zebrafish during embryonic development (39).…”
Section: Discussionmentioning
confidence: 98%
“…It has also been reported that miR-432-5p was implicated in facilitating cell progression by activating Wnt/β-catenin signaling and promoting cell growth and metastasis in human hepatocellular carcinoma (33,34). Yang et al reported that lower levels of miR-432-5p were observed in both glioma tissues and cells (35), and it has been extensively reported that translocation t(X;17)(p11;q25) of ASPSCR1 with transcription factor TFE3 gene results in a ASPSCR1-TFE3 fusion protein in alveolar soft part sarcoma and in renal cell carcinomas (36,37). ZNF384related fusion genes were detected in acute lymphoblastic leukemia (38), and GALNT9 was demonstrated to be well conserved in zebrafish during embryonic development (39).…”
Section: Discussionmentioning
confidence: 98%
“…Another study has suggested that miR-150-5p had a downstream target relationship with ZFAS1 in the regulation of melanoma malignancy [6]. Except that, Yang et al have demonstrated that miR‐432-5p expression was elevated after transfection with siRNA-ZFAS1 [21]. A finding has demonstrated that lncRNA GACAT3 performs as a molecular sponge for miR‐135a in glioma [22].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the LncRNA ZFAS1 promotes gastric cancer malignancy through targeting the microRNA-200b-3p/Wnt1 pathway and epigenetically repressing KLF2 and NKD2 [13] , [14] . Furthermore, many other targets in different cancers have also been identified, such as the miR-432-5p in glioma [15] , miR-135a in nasopharyngeal carcinoma [16] , miR-7-5p, miR-484, and miR-150-5p/VEGFA in colorectal cancer [17] , [18] , [19] , miR-646/NOB1 pathway and miR-486 in osteosarcoma [20] , [21] , miR-150-5p/RAB9A in melanoma [22] , miR-150-5p in head and neck squamous cell carcinomas [23] , miR-10a/SKA1 pathway in clear cell renal cell carcinoma [24] , miR-329 in bladder cancer [25] , and miR-940 in prostate cancer [26] .…”
Section: Introductionmentioning
confidence: 99%